Biosynthesis and potential applications of terpenes produced from microalgae - Costa, Jorge Alberto Vieira; Cassuriaga, Ana Paula Aguiar; Moraes, Luiza; Morais, Michele Greque (Bioresource technology reports, 2022)
Research on safer and more environmentally friendly processes and products has highlighted microalgae as a promising source of natural products, among which the majority are hydrocarbon molecules. Microalgae can modulate their metabolic pathways to produce compounds with high technological potential, especially when they are grown in unsuitable environments for crop cultures (i.e., wastewater, imbalanced nutritional sources, and different environmental conditions). Terpene production by microalgae has been the subject of several studies because they can be used as high-value-added products, such as fragrances and aromas, in the latest generation of biofuels. Thus, this review aims to detail the state-of-the-art microalgal hydrocarbons (terpenes), production metabolism, growing conditions that trigger the pool of molecules, and the application of microalgal-origin terpenes. [Display omitted] •Nutritional conditions are presented as terpene accumulation factors.•The metabolic pathways involved in terpene production are discussed.•Metabolic changes trigger changes in terpenoid production.•Advances in molecular biology are essential in the production of new terpenoids.•Technological barriers and new perspectives are presented.